Persepsi Masyarakat Terhadap Mutu Pondok Pesantren Nurul Jadid - Khoirul Anam; Achmad Humaidi; Iin Zainab; Abdullah Abdullah (Universitas Nurul Jadid, 2021)
AbstractThis paper aims to determine the public's perception of the quality of the Nurul Jadid Islamic boarding school. This study uses a type of field research with a qualitative research design. This study used field research. This research is descriptive qualitative with a phenomenological approach. The data collected consists of primary data and secondary data. The results showed that the community rated the quality of the Nurul Jadid Islamic boarding school as very good, this was based on the increasing number of students who entered and the level of trust and satisfaction of the community as an external customer (service user) of the pesantren.